2016
DOI: 10.1037/pspi0000062
|View full text |Cite
|
Sign up to set email alerts
|

Daily goal progress is facilitated by spousal support and promotes psychological, physical, and relational well-being throughout adulthood.

Abstract: In two daily-diary studies, we tested the consequences and precursors of daily goal progress throughout the adult lifespan. Attachment theory posits that exploration—including the pursuit of autonomous goals—promotes well-being across the lifespan and is facilitated by support from close others. For both young-adult newlyweds (Study 1) and married couples in late adulthood (Study 2), daily independent goal progress predicted same-day and next-day improvements in psychological, physical, and relational well-bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 107 publications
2
64
0
1
Order By: Relevance
“…Although few studies have examined links between positive forms of support and objective health outcomes, two diary studies showed that daily spousal support for goal strivings was associated with greater daily goal progress; and goal progress was associated with daily improvements in physical (sleep quality, somatic symptoms), psychological, and relational well-being (Jakubiak & Feeney, 2016a). More research is needed on the health implications of support received in the context of goal strivings, personal growth, and positive life experiences.…”
Section: Social Connection: Processes That Protect and Promote Healthmentioning
confidence: 99%
“…Although few studies have examined links between positive forms of support and objective health outcomes, two diary studies showed that daily spousal support for goal strivings was associated with greater daily goal progress; and goal progress was associated with daily improvements in physical (sleep quality, somatic symptoms), psychological, and relational well-being (Jakubiak & Feeney, 2016a). More research is needed on the health implications of support received in the context of goal strivings, personal growth, and positive life experiences.…”
Section: Social Connection: Processes That Protect and Promote Healthmentioning
confidence: 99%
“…For example, limited willpower theorists might have positive social interactions during times of low demand but be more likely to exhibit negative social behaviors when times get tough. Furthermore, dyadic goal pursuit—including the role of social support in goal pursuit (Jakubiak & Feeney, )—is also likely affected by willpower theories, as one person's goal striving impacts their partner's. If a limited theorist has poor self‐regulation during times of stress, their partner may experience negative effects as they try to accommodate the limited theorist.…”
Section: Everyday Outcomes Of Willpower Theoriesmentioning
confidence: 99%
“…Therefore, the current study will investigate intrusion, awareness, optimism, and pessimism as determinants of reducing discrepancies between goal importance and goal attainability. Additionally, there has been a growing research interest in the concept of goal progress (e.g., Beattie, Hardy, & Woodman, 2015;Harkin et al, 2016;Hope, Milyavskaya, Holding, & Koestner, 2016;Jakubiak & Feeney, 2016). Goal progress is defined as the perceived extent to which a personal goal is achieved and serves as feedback about how well people are doing (Locke, 1996).…”
Section: Statement Of Contributionmentioning
confidence: 99%